Senecavirus A: An Emerging Pathogen Causing Vesicular Disease and Mortality in Pigs?. (January 2017) - Segalés, J.; Barcellos, D.; Alfieri, A.; Burrough, E.; Marthaler, D.
Senecavirus A (SVA) is the only member of the genus Senecavirus within the family Picornaviridae. This virus was discovered as a serendipitous finding in 2002 (and named Seneca Valley virus 001 [SVV-001]) while cultivating viral vectors in cell culture and has been proposed for use as an oncolytic virus to treat different types of human neoplasia. SVA was found in lesions in pigs affected by porcine idiopathic vesicular disease in Canada and the USA in 2008 and 2012, respectively. In 2014 and 2015, SVA infection was associated with outbreaks of vesicular disease in sows as well as neonatal pig mortality in Brazil and the USA. Phylogenetic analysis of the SVA VP1 indicates the existence of 3 clades of the virus. Clade I contains the historical strain SVV-001, clade II contains USA SVA strains identified between 1988 and 1997, and clade III contains global SVA strains from Brazil, Canada, China, and the USA identified between 2001 and 2015. The aim of this review is to draw the attention of veterinarians and researchers to a recently described infectious clinical-pathologic condition caused by a previously known agent (SVA). Apart from the intrinsic interest in a novel virus infecting pigs and causing economic losses, the major current concern is the similarity of the clinical picture to that of other swine diseases, because one of them—foot and mouth disease—is a World Organization for Animal Health–listed disease. Because the potential association of SVA with disease is rather new, there are still many questions to be resolved.